2008
DOI: 10.2174/157489008783331689
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes: A Therapeutic Promise for Cardiovascular Diseases

Abstract: The research, development and use of natural products as therapeutic agents, especially those derived from plants, have been increasing in recent years. There has been great deal of focus on the naturally occurring antispasmodic phytochemicals as potential therapy for cardiovascular diseases. Naturally occurring diterpenes exert several biological activities such as anti-inflammatory action, antimicrobial and antispasmodic activities. Several diterpenes have been shown to have pronounced cardiovascular effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 37 publications
0
8
0
4
Order By: Relevance
“…Some studies have shown that kaurenoic acid inhibits the contractions induced by KCl and phenylephrine on rat carotid artery [15] . The aforementioned studies and others indicate the potential use of this diverse class of compounds in pharmacological therapies related to smooth muscle [16,17] …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some studies have shown that kaurenoic acid inhibits the contractions induced by KCl and phenylephrine on rat carotid artery [15] . The aforementioned studies and others indicate the potential use of this diverse class of compounds in pharmacological therapies related to smooth muscle [16,17] …”
Section: Introductionmentioning
confidence: 95%
“…[15] The aforementioned studies and others indicate the potential use of this diverse class of compounds in pharmacological therapies related to smooth muscle. [16,17] Owing to their importance in asthma physiopathology, respiratory smooth muscle contraction and airway inflammation constitute potential targets for therapeutic approaches but existing pharmacological interventions are limited by numerous problems such as tachyphylaxis, loss of efficacy and treatment side-effects. [18,19] Accordingly, identifying new bronchorelaxant agents and determining their mechanisms of action may lead to significant advances in asthma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Os terpenoides constituem um vasto grupo de substâncias químicas biossintetizadas a partir da via do mevalonato, extraídas de produtos naturais. Possuem diversas atividades biológicas bem definidas, dentre as quais a antifúngica 8,9,10 .…”
Section: Terpenoides Com Atividade Antifúngica Para Candida Berkhoutunclassified
“…Atualmente, uma tendência multidisciplinar vem contribuindo cada vez mais para o desenvolvimento de novas drogas. Tal estratégia inicia-se pela bioprospecção de substâncias naturais bioativas, extraídas principalmente de plantas ou de microrganismos, seguida pela tentativa de obtenção de seus análogos estruturais, o que pode ser realizado por métodos sintéticos ou biotecnológicos, que culminam com a avaliação de suas atividades farmacológicas, toxicológicas e determinação do mecanismo de ação 9,10 .…”
Section: Produtos Naturais Substâncias Bioativas E Potencial Antimicunclassified
See 1 more Smart Citation